Discrete choice experiment data for street-level urban greening in Berlin. - Fruth, Erik; Kvistad, Michele; Marshall, Joe; Pfeifer, Lena; Rau, Luisa; Sagebiel, Julian; Soto, Daniel; Tarpey, John; Weir, Jessica; Winiarski, Bradyn (Elsevier, 2020)
The data presented in this article are the outcome of a survey implemented in a Berlin neighborhood from January to March 2018. The data consist of socio-demographic, attitudinal and perception questions, and, most importantly, a discrete choice experiment. This dataset is complementary to the full research article, “Economic valuation of street-level urban greening: A case study from an evolving mixed-use area in Berlin”. The analysis of the discrete choice experiment provided in the full article could be used to guide policy- and project-level decision-making for green building practices and urban green initiatives, while the dataset available here can be used to provide insight about how the sample population responded to the remaining parts of the questionnaire and how the experiment could be replicated in context or elsewhere in Berlin.
Keywords: Stadtgrün; Partizipation; Stadtgestaltung; Ökosystem; Straßengrün; Datenanalyse; Entscheidungsverfahren; Lebensqualität; Mischgebiet